Gender Differences in Academic Stress among Higher Secondary School Students in Gujarat - Ghatol, Snehalata D. (JOURNAL OF INDIAN EDUCATION, 2021)
The present study was undertaken to investigate gender differences in academic stress with respect to gender differences among higher secondary school students in Anand district of Gujarat state. The study is based on primary data collected from the randomly selected 1000 sample students from 13 higher secondary schools (XI and XII). The study results indicate that there is a significant difference between the mean scores of academic stress in relation to boys and girls students of higher secondary school. The boys have high academic stress than the girls of higher secondary school. The comparison of boys and girls students across streams indicate that boys of the commerce stream have high academic stress than the girls students of higher secondary school, while the boys and girls students of science and arts stream does not indicate any significant difference in stress levels between them. Therefore, methods of overcoming stress cannot be the same for boys and girls, and methods should be based on the factors causing stress among the boys and girls rather than any other basis.